Open Reconstruction of Complex Proximal Metadiaphyseal Fragility Fractures of the Humerus. (March 2014) - James, Isaac B.; Farrell, Dana J.; Evans, Andrew R.; Siska, Peter A.; Tarkin, Ivan S.
Purpose: A proactive surgical and rehabilitation protocol was implemented to manage humeral fractures involving both the proximal end and shaft in an older patient population. Primary treatment goals were early return to function and reliable fracture union with minimal complications. Methods: From 2008 to 2012, 21 such operations were performed; 18 were considered "fragility" fractures based on mechanism, patient age, and evidence of osteopenia or osteoporosis. Open reduction and internal fixation ( ORIF ) was employed using direct reduction and fixation with a long periarticular locking plate. Physiotherapy was commenced 2 weeks postoperatively. The Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire was used to assess functional outcome at a time point greater than 1 year postoperative. Results: The study group consisted primarily of elderly females (83% with a median age of 69 years) whom sustained complex metadiaphyseal proximal humeral fractures after simple mechanical fall (78%). Uneventful union occurred in all cases. Local complications included 1 case of partial radial nerve palsy, which had resolved completely by 1 year. No cases of infection were identified. Long-term return to functionality was evident with a median DASH score of 12 (mean = 21, standard deviation = 20, n = 13). Seventy five percent of patients reported minimal or no pain (question [Q] 24), and 75% achieved return of overhead function (Q6, 12, and 15). Conclusion: Treatment of complex metadiaphyseal fragility fractures with anatomic reduction, fixed angle plating, and early physiotherapy returns the older patient to optimized functionality with minimal risk of complication. The DASH outcomes are equivalent to ORIF of isolated proximal humerus fractures and clinically indistinguishable from the general population.